Molecular expression profile reveals potential biomarkers and therapeutic targets in canine endometrial lesions - Voorwald, Fabiana Azevedo [UNESP]; Marchi, Fabio Albuquerque; Villacis, Rolando Andre Rios; Alves, Carlos Eduardo Fonseca [UNESP]; Toniollo, Gilson Hélio [UNESP]; Amorim, Renee Laufer [UNESP]; Drigo, Sandra Aparecida [UNESP]; Rogatto, Silvia Regina [UNESP] (Public Library Science, 2015)
Cystic endometrial hyperplasia (CEH), mucometra, and pyometra are common uterine diseases in intact dogs, with pyometra being a life threatening disease. This study aimed to determine the gene expression profile of these lesions and potential biomarkers for closed-cervix pyometra, the most severe condition. Total RNA was extracted from 69 fresh endometrium samples collected from 21 healthy female dogs during diestrus, 16 CEH, 15 mucometra and 17 pyometra (eight open and nine closed-cervixes). Global gene expression was detected using the Affymetrix Canine Gene 1.0 ST Array. Unsupervised analysis revealed two clusters, one mainly composed of diestrus and CEH samples and the other by 12/15 mucometra and all pyometra samples. When comparing pyometra with other groups, 189 differentially expressed genes were detected. SLPI, PTGS2/COX2, MMP1, S100A8, S100A9 and IL8 were among the top up-regulated genes detected in pyometra, further confirmed by external expression data. Notably, a particular molecular profile in pyometra from animals previously treated with exogenous progesterone compounds was observed in comparison with pyometra from untreated dogs as well as with other groups irrespective of exogenous hormone treatment status. In addition to S100A8 and S100A9 genes, overexpression of the inflammatory cytokines IL1B, TNF and IL6 as well as LTF were detected in the pyometra from treated animals. Interestingly, closed pyometra was more frequently detected in treated dogs (64% versus 33%), with IL1B, TNF, LBP and CXCL10 among the most relevant overexpressed genes. This molecular signature associated with potential biomarkers and therapeutic targets, such as CXCL10 and COX2, should guide future clinical studies. Based on the gene expression profile we suggested that pyometra from progesterone treated dogs is a distinct molecular entity.